2020
DOI: 10.15407/zoo2020.01.017
|View full text |Cite
|
Sign up to set email alerts
|

New records of hover flies (Diptera, Syrphidae) from Ukraine. IV

Abstract: New Records of Hover fl ies (Diptera, Syrphidae) from Ukraine. IV. Prokhorov, A. V., Popov, G. V., Shparyk, V. Yu. -Six additional species of hover fl ies of the subfamily Eristalinae are recorded from Ukraine for the fi rst time: these species are summarized and species diagnoses are provided. Updated key to males of the European species of the genus Melanogaster including a little-known M. jaroslavensis (Stackelberg, 1922) is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Th ompson & Rotheray (1998) also included Hammerschmidtia Schummel, 1834 in the genus Brachyopa due to very similar morphological features of their imago and larva. An on-going study of the hoverfl y fauna of the Ukraine has found eight species of Brachyopa and one species of Hammerschmidtia (Prokhorov et al, 2018(Prokhorov et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Th ompson & Rotheray (1998) also included Hammerschmidtia Schummel, 1834 in the genus Brachyopa due to very similar morphological features of their imago and larva. An on-going study of the hoverfl y fauna of the Ukraine has found eight species of Brachyopa and one species of Hammerschmidtia (Prokhorov et al, 2018(Prokhorov et al, , 2020.…”
Section: Introductionmentioning
confidence: 99%